Sistem Pemantauan Kualitas Udara Portable Menggunakan GPS Berbasis Internet of Things - Aziz, Abdul; Rafif, Muhammad; Nurjihan, Shita Fitria; Nixon, Benny (Spektral, 2025)
As a natural resource, air plays a vital role in sustaining life. Clean air provides significant benefits to living things, while polluted air can disrupt the balance of the ecosystem. Sources of air pollution include motor vehicle exhaust, fossil fuel-based industrial activities, and forest fires. Maintaining clean air quality requires an air quality monitoring device. With the development of Internet of Things (IoT) technology, this study designed a portable IoT-based air quality monitoring device using a GPS module, MQ-2, MQ-135, MQ-136 sensors, and an LTE module. This device is designed to be easily carried to various locations. The GPS module is used to obtain precise location data, while the integrated air quality sensor will measure parameters such as particulate concentration, toxic gases, and air humidity. The data displayed on the air quality monitoring device are CO, CO2, SO2 values, and location coordinates. The received air quality data complies with the ISPU (Air Pollution Standards Index) standard. Test results show that the sensor can read measurement values ​​with air quality categories of "Good," "Moderate," and "Unhealthy." The Android application can also display test data sent from the Firebase real-time database to the Android application for CO, CO2, SO2, Longitude, Latitude, time, and date.